ГДЗ до підручника «Алгебра» А.Г. Мерзляка. 7 клас

4) a2nb3n - anb4n = anb3n(an - bn).

1162. 1) Якщо a = 5,28, to a2 + 4,72a - 32,8 = a(a + 4,72) - 32,8 = 5,28 • (5,28 + 4,72) - 32,8 = 5,28 • 10 - 32,8 = 52,8 - 32,8 = 20.

2) Якщо x - 8,14, у = 8,04, то 12,3х - 12,3y + 4,7 = 12,3(х - у) + 4,7 = 12,3 • (8,14 - 8,04) + 4,7 = 12,3 • 0,1 + 4,7 = 1,23 + 4,7 = 5,93.

1163. 1) 2,49 • 1,35 - 1,35 • 1,84 + 1,352 = 1,35 • (2,49 - 1,84 + 1,35) = 1,35 • (3,84 - 1,84) = 1,35 • 2 = 2,7;

2) 0,252 • 1,6 + 0,25 • 1,62 - 0,25 • 1,6 • 0,85 = 0,25 • 1,6 • (0,25 + 1,6 - 0,85) = 0,4 • 1 = 0,4;

3) 3,24 • 18,7 - 3,24 • 16,4 + 2,3 • 6,76 = 3,24 • (18,7 - 16,4) + 2,3 • 6,76 = 3,24 • 2,3 + 2,3 • 6,76 = 2,3 • (3,24 + 6,76) = 2,3 • 10 = 23;

4) 5,12 • 9,76 + 5,12 • 5,36 - 5,122 = 5,12 • (9,76 + 5,36 - 5,12) = 5,12 • 10 = 51,2.

1164. 1) 173 + 172 - 17 = 17 • (172 + 17 - 1) = 17 • 305 — кратне 61, бо 305 кратне 61;

2) 254 - 1252 = (52)4 - (53)2 = 58 - 56 = 56 • (52 - 1) = 56 • 24 = 55 • 5 • 8 • 3 = 55 • 3 • 40 — кратне 40;

3) 66 - 183 = 66 - 63 • 33 = 63 • (63 - 33) = 63 • (216 - 27) = 63 • 189 = 62 • 6 • 7 • 27 = 62 • 42 • 27 — кратне 42;

4) 5 • 2962 - 3 • 2961 + 2960 = 2960 • (5 • 22 - 3 • 2 + 1) = 2960 • (20 - 6 + 1) = 2960 • 15 = 2958 • 22 • 15 = 2958 • 60 — кратне 60.

1166. (х + 2)(х - 4) - (х - 2)(х + 4) = ах; х2 + 2х - 4х - 8 - х2 + 2х - 4х + 8 - ах = 0; -4х - ах = 0; -х(4 + а) = 0. Рівняння має безліч коренів, коли 4 + а = 0, тобто а = -4.

1168. 1) хm - хn + уm - уn = х(m - n) + у(m - n) = (m - n)(х + у);

2) 3а - 3b + ас - bс = 3(а - b) + с(а - b) = (а - b)(3 + с);

3) 9a - ab - 9 + b = a(9 - b) - (9 - b) = (9 - b) • (а - 1);

4) а5 + а3 + 2а2 + 2 = а32 + 1) + 2(а2 + 1) = (а2 + 1)(а3 + 2);

5) 6аb2 - 3b2 + 2а2b - ab = 3b2(2а - 1) + аb(2а - 1) = (2а - 1)(3b2 + ab) = b(2а - 1) • (3b + а);

6) 2с3 - 5c2d - 4с + 10d = с2(2с - 5d) - 2(2c - 5d) = (2с - 5d)(c2 - 2);

7) х3у2 - х + х2у3 - у = х(х2у2 - 1) + у(х2у2 - 1) = (х2у2 - 1)(х + у) = (ху - 1)(ху + 1) • (x + у);

8) ах2 - ay - су + bx2 + сх2 - by = (ах2 - ау) + (bx2 - by) + (сх2 - су) = а(х2 - у) + с(х2 - у) + b(х2 - у) = (х2 - у)(а + с + b).

1169. 1) 1,662 + 1,66 • 4,68 + 2,342 = 1,662 + 2 • 1,66 • 2,34 + 2,342 = (1,66 + 2,34)2 = 42 = 16;

2) 1,042 - 1,04 • 1,28 + 0,642 = 1,042 - 2 • 1,04 • 0,64 + 0,642 = (1,04 - 0,64)2 = 0,42 = 0,16.